COMM 111 - Public Speaking - John Drischell (2021)
This course exposes students to theory and practice in the creation, adaptation and delivery of original speeches before an audience. It also provides the opportunity to understand the nature of public speaking and discourse in both ancient and modern society. Upon successful completion of this course, students will be able to: Synthesize, organize information for varied audiences. Interact with confidence while adapting messages to audience needs. Listen critically.